Experimental study of suddenly expanded flow from correctly expanded nozzles - Khan, Sher Afghan; G M, Fharukh Ahmed (Department of Mechanical Engineering Saveetha School of Engineering Saveetha University, 2016)
This paper presents the results of the experimental investigation conducted at supersonic Mach numbers through converging–diverging nozzles. The experiments were conducted for correctly expanded cases and, for length-to-diameter ratio of 10 to 1. The area ratios were 1.6, 1.8, 2.2, and 6.25. The results presented are only for correctly expanded jets. From the results it is found that at lower Mach numbers and area ratios the efficacy of the control in the form of micro jets is only marginal and the control results in increase of base pressure for all the Mach number for the first two lower area ratios namely 2.56 and 3.24, it is also observed that the magnitude is getting enhanced considerably from Mach 1.6 and beyond, but for the larger area ratios namely 4.84 and 6.25 of the present study the control results in decrease of base pressure for Mach numbers in the range 1.6, 1.8, and 2.0. When we analyzed and plotted the wall pressure distribution in the enlarged duct the flow remains unperturbed and attached with the suddenly expanded duct for both with and without control cases. For Mach 1.48 the flow field in the duct becomes oscillatory which; indicates that the flow in the duct is dominated by the waves and when the active control is employed suppresses the noise, and this peculiar phenomenon happens only for this Mach number. However, for Mach 1.8 and 2.0 the flow structure in the duct remained oscillatory for the entire region of the duct, and for rest of the Mach numbers it remained same even when the control in the form of micro jets are activated. Hence, it can be stated that the control with the micro jets does influence the flow in the duct wall adversely except at Mach 1.48.